1997
DOI: 10.1074/jbc.272.50.31241
|View full text |Cite
|
Sign up to set email alerts
|

COL1A1 Transgene Expression in Stably Transfected Osteoblastic Cells

Abstract: Collagen reporter gene constructs have be used to identify cell-specific sequences needed for transcriptional activation. The elements required for endogenous levels of COL1A1 expression, however, have not been elucidated. The human COL1A1 minigene is expressed at high levels and likely harbors sequence elements required for endogenous levels of activity. Using stably transfected osteoblastic Py1a cells, we studied a series of constructs (pOBColCAT) designed to characterize further the elements required for hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…To create the promoter deletion constructs pColCAT Ϫ1.3/ϩ1.6 and Ϫ0.4/ϩ1.6, B16 was digested with NheI (Ϫ3382) together with Tth111I (Ϫ1282) or MunI (Ϫ390), respectively, and religated. The intron-less pColCAT Ϫ2.3/0 is identical to B47 (17) except that it lacks the 5Ј HindIII fragment between Ϫ3544 and Ϫ2369 present in B16.…”
Section: Cells and Culture Conditionsmentioning
confidence: 97%
“…To create the promoter deletion constructs pColCAT Ϫ1.3/ϩ1.6 and Ϫ0.4/ϩ1.6, B16 was digested with NheI (Ϫ3382) together with Tth111I (Ϫ1282) or MunI (Ϫ390), respectively, and religated. The intron-less pColCAT Ϫ2.3/0 is identical to B47 (17) except that it lacks the 5Ј HindIII fragment between Ϫ3544 and Ϫ2369 present in B16.…”
Section: Cells and Culture Conditionsmentioning
confidence: 97%
“…This plasmid construct is identical to B15, described by Breault et al (29), except an EcoRV site in the polylinker has been converted to a ClaI site. The construct contains sequences between Ϫ3518 and ϩ1594 (relative to the transcription start site) of the rat COL1A1 gene, which includes the upstream promoter region, the first exon (the translational start site, ATG, has been converted to a NotI site), and most of the first intron (3.6/1.6 refers to 3.6 kb of upstream promoter sequence and 1.6 kb of downstream sequence).…”
Section: Cell Culture and Cyclic Mechanical Strain Applied To Fibroblmentioning
confidence: 99%
“…The full-length construct, pColCAT-3.6/1.6, contains 3.6 kb of the 5Ј upstream promoter sequence and 1.6 kb of sequence downstream of the transcription start site, including the first exon and most of the first intron. This construct was chosen because these regions of the COL1A1 gene, including the first intron, are known to contain potentially important positive and negative regulatory sequences (29,(35)(36)(37), and it therefore provides a suitable starting point for modeling responses of the endogenous gene. Cells transfected with the full-length pColCAT-3.6/1.6 construct displayed an ϳ2-fold increase in CAT protein levels in response to continuous cyclic strain for 48 h compared with rigid control cells.…”
Section: Cyclic Mechanical Strain Of Cardiac Fibroblasts Leads Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that interfering with the first intron of ␣1(I) collagen mRNA can have deleterious effects on collagen expression (25)(26)(27). Although these studies dealt with deletions in the first intron, evidence suggests that increased intron size can also influence transcript expression (28,29).…”
Section: Removal Of the Neo Cassette Had No Effect On ␣1(i) Collagenmentioning
confidence: 99%